Connections Between Stratospheric Ozone Concentrations Over the Arctic and Sea Surface Temperatures in the North Pacific. Issue 4 (15th February 2020) - Liu, Meichen; Hu, Dingzhu; Zhang, Feng
Abstract: We examined the relationship between sea surface temperatures (SSTs) in the North Pacific and the concentration of stratospheric ozone in the northern hemisphere in February–March from 1980 to 2017 using reanalysis and satellite datasets. Our results show that the concentration of stratospheric ozone can be modulated by the principle mode of the North Pacific SSTs—that is, there are negative and zonally asymmetrical ozone anomalies in the Arctic stratosphere, but positive ozone anomalies in the lower stratosphere at mid‐latitudes during the positive phases of the North Pacific SSTs. The North Pacific SST anomalies account for about 20% of the linear variance of ozone concentrations in the lower stratosphere over the Arctic. Negative SST anomalies in the central North Pacific tend to result in a strengthened Western‐Pacific like teleconnection, which favors the propagation of more planetary wavenumber‐1 and ‐2 waves into the stratosphere. The North Pacific SSTs‐related upwelling branch of the Brewer–Dobson circulation in the mid‐latitude stratosphere strengthens, but its downwelling branch in the Arctic stratosphere weakens. This results in decreased ozone anomalies in the lower stratosphere over the Arctic and increased ozone anomalies in the lower stratosphere at mid‐latitudes. The zonally asymmetrical distribution of ozone related to the positive phase of SSTs over the North Pacific may be related to the shifting and strengthening of the stratospheric Arctic vortex. Key Points: The concentration of stratospheric ozone over the Arctic can be modulated by SSTs in the North Pacific Negative SST anomalies in the central North Pacific weaken BD circulation over the Arctic by altering propagation of planetary waves The ozone anomalies modulated by SSTs in the the North Pacific are related to the anomalous Brewer–Dobson circulation and the polar vortex